Synergy of Training and Assistance for Beginner Entrepreneurs among Graduates of Bunda Produktif Institut Ibu Profesional Sumatera Utara - Sari, Elva Citra; Dalimunthe, Ritha F.; Harahap, R. Hamdani (Indonesian Journal of Advanced Research, 2025)
This study explores the synergy model of training and assistance for beginner entrepreneurs in the Bunda Produktif program by Institut Ibu Profesional Sumatera Utara. Using a qualitative approach, data were collected through in-depth interviews, observations, documentation, and focus group discussions. Thematic analysis was conducted using NVivo 15. Findings indicate that the program’s success is driven by the synergy of community-based training, continuous assistance, and the use of digital platforms. The program effectively enhances participants’ productivity, self-efficacy, and economic and social contributions. Key success factors include facilitator competence, community involvement, and digital access, while challenges include time management, financial independence, and limited post-program activities. The study recommends developing an adaptive, passion-based training and assistance model integrated with a digital monitoring system for sustainability and replication.